2013
DOI: 10.1126/science.1216260
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Minerals: Self-Assembled Calcite Spicules with Extreme Bending Strength

Abstract: Silicatein-α is responsible for the biomineralization of silicates in sponges. We used silicatein-α to guide the self-assembly of calcite "spicules" similar to the spicules of the calcareous sponge Sycon sp. The self-assembled spicules, 10 to 300 micrometers (μm) in length and 5 to 10 μm in diameter, are composed of aligned calcite nanocrystals. The spicules are initially amorphous but transform into calcite within months, exhibiting unusual growth along [100]. They scatter x-rays like twinned calcite crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 29 publications
1
141
0
7
Order By: Relevance
“…As a substrate in this work we have chosen to use the (1014) surface of calcite (CaCO 3 ), which is an important material in biomineralization [17][18][19]. It has also been previously considered in high resolution AFM experiments [20][21][22] and simulations in liquids [23,24] due to its stability and candidacy as a benchmark system-even for some of the earliest AFM pioneers [25].…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…As a substrate in this work we have chosen to use the (1014) surface of calcite (CaCO 3 ), which is an important material in biomineralization [17][18][19]. It has also been previously considered in high resolution AFM experiments [20][21][22] and simulations in liquids [23,24] due to its stability and candidacy as a benchmark system-even for some of the earliest AFM pioneers [25].…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…Moreover, ACC emerges frequently in the formation of CaCO 3 fibers [24,28,34,38,39]. Accordingly, in immature nanowires, we found an ACC layer (Figs.…”
Section: Resultsmentioning
confidence: 56%
“…Generally, the formation of anisotropic crystals can be achieved via tuning of the surface energy of crystal faces by changing the temperature and pH, or by adding specific molecules as modifiers [21][22][23][24][25]. An alternative method is to use prefabricated templates with designed shapes and surface functional groups [26][27][28][29].…”
mentioning
confidence: 99%
“…In sponges, the individual spicules are connected either by spongin-like fibrous molecules or DUF protein ) (as in demosponges) or are even fused together, like in hexactinellids (see Wang et al 2012). Our recent studies revealed that calcareous spicules, fabricated with silicatein from siliceous sponges, are characterized by exceptionally stabile and flexible properties (Natalio et al 2013). These observations suggest that sponges can react to both exogenous light (environmental day light) and endogenous light (via the luciferase system; Müller et al 2009).…”
Section: Introductionmentioning
confidence: 99%